Transplanting the Right of Publicity as a Property Right over AI Voice Cloning: A Comparative Analysis of Indonesia, Thailand, the US, and the EU - Hariyanto, Rodger Lui; Weley, Nadia Carolina; Hutauruk, Rufinus Hotmaulana (SIGn Jurnal Hukum, 2026)
The exploitation of voice identity by artificial intelligence development and user companies through voice cloning technology has caused tangible economic losses. The fundamental issue lies within the positive legal systems in Indonesia and Thailand, which experience qualification barriers. Civil instruments such as torts become paralyzed because cyber law, intellectual property, and data protection regimes fail to classify voice as a commercial property right object. Therefore, this research aims to comparatively analyze these civil law qualification barriers using the United States and the European Union as benchmarks, while simultaneously formulating a prescriptive transplantation of the right of publicity doctrine. This normative legal research utilizes the statute approach, comparative approach, and conceptual approach to comprehensively dissect domestic instruments and foreign case law. The results of the comparative analysis affirm the United States’ supremacy in recognising voice as a property right. This protection standard is refined by an ethical restriction layer in the form of an absolute prohibition as a default prohibition from the European Union. Overcoming domestic paralysis requires reconceptualizing property boundaries within the Civil Code. Recognizing voice as an intangible property will directly activate the tort lawsuit instrument. This activation aims to demand the disgorgement of profits from entities that develop artificial intelligence without authorisation and train algorithms without authorisation. This lawsuit also applies to commercial user entities conducting advertising through voice cloning. This research concludes that the adoption of the right of publicity requires the formulation of specific regulations (lex specialis) to protect personality rights. These regulations must explicitly separate corporate liability and adopt a layered consent standard. These rules must also contain a fair use exception to maintain a balance between economic property protection and freedom of expression in society.